2013
DOI: 10.1371/journal.pone.0073768
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Induced proNGF Synthesis and Release in the N9 and BV2 Microglial Cells: A New Pathway Underling Microglial Toxicity in Neuroinflammation

Abstract: PurposeWhile aberrant activation of microglial cells was evidently involved in neuroinflammation and neurotoxicity in the neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease, objective of study was to address if activated microglias deliver their effect by releasing pro-neurotrophins.Materials and methodsBy in vitro culture of N9 and BV2 cell lines and lipopolysaccharide (LPS) stimulation model, generation and release of proNGF, proBDNF and MMP-9 was studied in the activated microglial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
3
16
0
1
Order By: Relevance
“…The different proBDNF and proNGF expression patterns suggest diverse and independent mechanisms of regulation induced by anti-VEGF administration. This condition supports other findings, demonstrating that NGF and BDNF transcription, as well as proNGF and proBDNF expression, can be distinctly different in terms of time-course and spatial pattern, also following the same stimuli (Duan et al, 2013;Meyer, Matsuoka, Wetmore, Olson, & Thoenen, 1992;Noga et al, 2005). Furthermore, it is possible to speculate that proBDNF increase could represent a specific feedback mechanism to hinder the alterations induced by anti-VEGF agents which, unfortunately, may be not functional because of the downregulation of neurotrophins receptor expression/activation.…”
Section: Discussionsupporting
confidence: 91%
“…The different proBDNF and proNGF expression patterns suggest diverse and independent mechanisms of regulation induced by anti-VEGF administration. This condition supports other findings, demonstrating that NGF and BDNF transcription, as well as proNGF and proBDNF expression, can be distinctly different in terms of time-course and spatial pattern, also following the same stimuli (Duan et al, 2013;Meyer, Matsuoka, Wetmore, Olson, & Thoenen, 1992;Noga et al, 2005). Furthermore, it is possible to speculate that proBDNF increase could represent a specific feedback mechanism to hinder the alterations induced by anti-VEGF agents which, unfortunately, may be not functional because of the downregulation of neurotrophins receptor expression/activation.…”
Section: Discussionsupporting
confidence: 91%
“…Iba-1 protein is expressed in microglia [ 57 ], and is a microglia-specific calcium-binding protein that also participates in phagocytosis [ 58 ]. Ito et al [ 59 ] demonstrated that Iba-1 expression is related to microglial activation in the ischemic brain, and the physiological roles of activated microglia can be evaluated by determining the expression of Iba-1 [ 59 , 60 , 61 ]. Based on our results, we concluded that hypoxia led to the activation of microglia and that resveratrol (25 μM) reduced the activation of hypoxia-injured microglia.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that due to oxidative stress, processing and maturation of proNGF is impaired in the diabetic milieu, resulting in increased proNGF and decreased NGF levels in serum and ocular fluids from patients with proliferative diabetic retinopathy [5,6]. Furthermore, accumulation of proNGF has been reported in neurodegenerative diseases including Alzheimer’s Disease [11], Down’s syndrome [32] and myocardial infarction [33] as well as models of neuronal ischemic injury [34,35]. Therefore, there is a pressing need of rodent models that stably express a non-cleavable form of proNGF to better understand the impact of its accumulation in various tissues.…”
Section: Discussionmentioning
confidence: 99%